2009
DOI: 10.1128/aem.00156-09
|View full text |Cite
|
Sign up to set email alerts
|

The Haloprotease CPI Produced by the Moderately Halophilic Bacterium Pseudoalteromonas ruthenica Is Secreted by the Type II Secretion Pathway

Abstract: The gene (cpo) encoding the extracellular protease CPI produced by the moderately halophilic bacterium Pseudoalteromonas ruthenica CP76 was cloned, and its nucleotide sequence was analyzed. The cpo gene encodes a 733-residue protein showing sequence similarity to metalloproteases of the M4 family. The type II secretion apparatus was shown to be responsible for secretion of the haloprotease CPI.Moderately halophilic microorganisms include a broad variety of bacteria that are able to grow in media containing a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Recently, it was reported that the haloprotease CPI from the moderately halophilic bacterium Pseudoalternomonas ruthenica is exported by the Sec-dependent type II secretion system (27). Thus, it seems apparent that the mechanisms used by halophilic prokaryotes to deliver extracellular proteases are not conserved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was reported that the haloprotease CPI from the moderately halophilic bacterium Pseudoalternomonas ruthenica is exported by the Sec-dependent type II secretion system (27). Thus, it seems apparent that the mechanisms used by halophilic prokaryotes to deliver extracellular proteases are not conserved.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the maturation mechanism of the Sec-dependent subtilisin-like proteases secreted by the hyperthermophilic archaeon Thermococcus kodaraensis have been extensively characterized (8,33). Many halophilic bacteria and archaea produce extracellular proteases, however, there is limited information on the pathways used by halophiles to deliver secretory proteases (27,28), and the mechanism that leads to enzyme activation has not been examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strain CP76 was isolated from a saltern located in Isla Cristina (Huelva, Spain). This strain is moderately halophilic (7), and the biochemical and molecular features of the protease, designated haloprotease CPI, were studied in detail (5, 8). It has a molecular mass of 38.0 kDa and showed optimal activity at 55°C, pH 8.5 (range, 6 to 10), and 7.5% NaCl (range, 0 to 4 M) (5).…”
Section: Genome Announcementmentioning
confidence: 99%
“…A detailed taxonomic study placed strain CP76 within the species Pseudoalteromonas ruthenica (9). The cpo gene encoding the extracellular haloprotease CPI was cloned and its nucleotide sequence was analyzed (8). It encodes a 733-residue protein showing sequence similarity to metalloproteases of the M4 family (zincins superfamily).…”
Section: Genome Announcementmentioning
confidence: 99%